Efficacy and Safety of Evobrutinib in Relapsing Multiple Sclerosis: A Systematic Review of Randomized Controlled Trials - Edeline Samudra; Anyeliria Sutanto (Magna Neurologica, 2025)
Background: Evobrutinib is a selective Bruton’s tyrosine kinase (BTK) inhibitor that crosses the blood-brain barrier. BTK regulates B lymphocytes and myeloid cells, significantly contributing to multiple sclerosis (MS) inflammation. While current MS treatments alleviate relapses and disability, they have a limited impact on inflammation within the central nervous system. Objective: We aim to evaluate the efficacy and safety of evobrutinib in relapsing MS. Methods: A systematic search of databases, including PubMed, Elsevier, NEJM, BMJ Journals, and Neurology, was conducted. Inclusion criteria: Studies within 5 years, randomized controlled trials, and interventions with evobrutinib. Exclusion criteria: Incomplete reporting, non-phase two trials, and JADAD score < 3. The quality of the included studies was evaluated using the JADAD scale. Results: The literature search yielded 552 studies, of which eight were included in the final analysis. All studies consistently demonstrated significant benefits in reducing disease activity. The efficacy of evobrutinib 75 mg BID showed a significant reduction in ARR (mean ARR = 0.10) and gadolinium-enhancing lesions compared to placebo (mean ARR = 0.37). SEL volume was significantly reduced, especially in patients with higher disability and longer disease duration. The safety profile of evobrutinib was comparable to that of a placebo, with similar rates of TEAEs. Liver enzyme elevations were noted in one study but were generally manageable. Stability in EDSS scores over extended treatment periods suggests effective disease control. Conclusion: Evobrutinib is a promising therapeutic option for managing MS, particularly relapsing forms, due to its efficacy in reducing disease activity and favorable safety profile.